2022
DOI: 10.1002/rmb2.12441
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome analysis in women with endometriosis: Does a microbiome exist in peritoneal fluid and ovarian cystic fluid?

Abstract: Purpose To investigate the relationship between the microbiome of the female genital tract and endometriosis. Methods This prospective cohort study included 36 women who underwent laparoscopic surgery for ovarian tumor from July 2019 to April 2020. Of them, 18 had endometriosis, and 18 did not have endometriosis. Vaginal secretions, endometrial fluid, peritoneal fluid, and ovarian cystic fluid were collected during surgery. Next‐generation sequencing of bacterial 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The inclusion criteria for the study, were as follows (1): all observational studies (including case-control, cross-sectional, prospective, and retrospective cohort studies or interventional studies) (2); women with HPV infection (HPV+), HPV persistence, low-grade squamous intraepithelial lesions (LSIL), HSIL, and Ca – categorized according to the results of HPV testing and histology of cervical biopsy, compared to healthy controls (HPV-negative and cytology-negative women) or HPV-negative women (HPV-), cervical cytology was used for classification if histology was not reported (3); studies reporting microbiota analyses of vaginal samples based on high-throughput sequencing ( 4 ); studies with information on vaginal microbial alterations at the community level (alpha and beta diversity) and/or taxonomic levels (relative abundance of different microbial species).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria for the study, were as follows (1): all observational studies (including case-control, cross-sectional, prospective, and retrospective cohort studies or interventional studies) (2); women with HPV infection (HPV+), HPV persistence, low-grade squamous intraepithelial lesions (LSIL), HSIL, and Ca – categorized according to the results of HPV testing and histology of cervical biopsy, compared to healthy controls (HPV-negative and cytology-negative women) or HPV-negative women (HPV-), cervical cytology was used for classification if histology was not reported (3); studies reporting microbiota analyses of vaginal samples based on high-throughput sequencing ( 4 ); studies with information on vaginal microbial alterations at the community level (alpha and beta diversity) and/or taxonomic levels (relative abundance of different microbial species).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has indicated a close relationship between the microbiome of the lower genital tract and gynecological diseases, such as polycystic ovary syndrome (PCOS), endometriosis, and HPV-related cervical diseases. Bacterial vaginosis-related (BV) microbes have been detected in PCOS and endometriosis in previous studies (3,4). Epidemiological studies have identified relationships between vaginal dysbiosis and HPV-related diseases, particularly in BV, in relation to the risk factors involved in the initiation and progression of HPV infection (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of clinical studies investigating the microbiota associated with endometriosis are listed in Table 1 . 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 Advances in NGS have led to the bacterial analysis of female genital organs since 2016. The genital microbiota, especially in the endometrium, which was previously thought to be sterile, is increasingly being studied in the field of endometrial receptivity, implantation, and placentation 63 , 64 and is also being examined to reveal the cause of endometriosis, recently.…”
Section: Emergence Of Bacterial Factorsmentioning
confidence: 99%
“…The majority of the clinical studies investigating endometriosis and microbiome changes were derived from Asia including Japan, China, Taiwan, Korea, and Turkey ( Table 3 , Supplementary Table S1 ) [ 21 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. There were also some studies from the United States, Brazil, Sweden, and Canada [ 119 , 120 , 121 , 122 , 123 ].…”
Section: The Intricate Relationship Between the Female Reproductive T...mentioning
confidence: 99%
“…Once thought to be “sterile”, the peritoneal microbiome is found to be associated with the etiology of diseases such as end-stage kidney disease and cancer [ 125 , 126 , 127 ]. As such, it is certainly logical to investigate the changes in the peritoneal microbiome among endometriosis patients, given that the lesion may involve the peritoneum [ 110 , 116 , 128 ]. In 2022, Yuan et al reported that there was a total of 276 operational taxonomic units (OTUs) detected in peritoneal fluid collected from endometriosis patients (as compared to 211 OTUs in the control group); out of which, 120 of them were unique to endometriosis group [ 117 ].…”
Section: The Intricate Relationship Between the Female Reproductive T...mentioning
confidence: 99%